The Contribution of CMS Missionaries to the Educational, Cultural and Spiritual Advancement of the People of Jaffna - Daniel Jeyaruban, V. (University of jaffna, 2024)
This study delves into the substantial contribution of CMS Missionaries to the educational, cultural, and spiritual development of the people of Jaffna during the 19th and 20th centuries. The 19th century is often labeled as the era of the Protestant Mission by Church historians. Many missionaries from Europe and America, including the CMS, ventured into Asia and Africa to spread the Christian Gospel. The CMS, an Anglican Church wing, initiated work in Jaffna in 1818, significantly influencing the region’s progress. Despite accusations that the CMS aimed to promote British culture, it’s crucial to note that missions in the 19th century, including the CMS, believed in the superiority of Western culture. The CMS played a pivotal role in disseminating Western values, impacting Jaffna’s people. They became highly educated in English, exhibited a strong interest in social welfare, and produced notable individuals like SJV Chelvanayagam and Dr. E N P Naganathan, known for their courage, determination, fortitude, and commitment. This objective study acknowledges that while the CMS might not have shown much interest in indigenous culture, its impact led to the emergence of individuals with sterling qualities, influenced by Western civilizations and culture. The contribution of CMS missionaries to the educational, cultural, and spiritual advancement of Jaffna is significant. This research addresses a crucial gap, as no in-depth study has focused on CMS’s contribution in Jaffna. Unlike other missions, the CMS firmly believed in imparting Western culture, evident in the thoroughness and commitment with which they approached this task. The CMS was instrumental in advancing English education in Jaffna. Principals of CMS institutions, educated in renowned English schools and colleges, believed education was the key to progress. The study highlights that not only Roman Catholic, American, and Methodist missionaries but also CMS significantly contributed to Jaffna’s cultural, spiritual, and educational development. The missionaries advocated for education for all, regardless of caste or gender. By establishing village schools and promoting vernacular education, they dismantled these barriers, empowering marginalized communities. The CMS’s work made the people of Jaffna versatile, sophisticated, and socially conscious. The holistic education provided by CMS institutions, which includes not only academic learning but also involvement in extracurricular activities and the development of leadership qualities, prepares students to be well-rounded and capable individuals. Despite criticisms leveled against Christian missions, this study shows the all-round contribution of CMS to the cultural, spiritual, and educational advancement of the region. The influence of CMS missionaries as educators, principals, and teachers left lasting legacies that endure over time. Despite early criticisms, this study demonstrates that CMS missionaries gradually recognized the value of indigenous religion, contributing to the cultural understanding of the people ofJaffna. In examining the schools established and publications compiled by CMS, this research sheds light on the comprehensive impact of CMS Missionaries in Jaffna’s educational, cultural, and spiritual landscape.
Keywords: Missionaries; Protestant; Empower; Superiority; Institution